MANAGEMENT OF DIFFICULT AIRWAY BY RETROGRADE ENDOTRACHEAL INTUBATION IN CARDIAC SURGERY PATIENT: Difficult Airway & Endotracheal Intubation - Ahmed, Col Iftikhar; Akhtar, Fahmida; Zameer, Muhammad (Pakistan Armed Forces Medical Journal, 2010)
Anesthesiologists rarely encounter patients in their practice in whom tracheal intubation is either extremely difficult or impossible. The problem of difficult intubation and its management is more challenging in cardiac surgical patients who are usually in compromised cardiac and respiratory state and require tackling with minimum haemodynamic upset1. The importance of pre-operative assessment of anticipated difficulty its, degree and plan to manage can not be over emphasized2. Realizing the gravity of the problems, different techniques have been adopted with their merits and demerits3. We report a case of difficult rather impossible intubation by retrograde catheter method in coronary artery bypass grafting.